Political Repression: A Comparative Study - Jasim, Ahmed (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: This paper analyzes the differences as well as similarities between Pinter’s “One for the Road” and Abd Sabur‘s “Night Traveller” that deal with the theme of suppression within the critical framework of the “Theatre of the Absurd”. I argue in my present research that the two plays named above are necessarily oppressive, enriched with an oppressor-oppressed dynamic. In such cases, the suppressor uses all available resources to keep the oppressed quiet. Nonetheless, if both plays are viewed through a “theatre of the Oppressed”, then they may be able to revolt Against Systematic suppression.